2016
DOI: 10.1002/humu.23019
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Missense Variants in the Putative Breast Cancer Susceptibility GeneXRCC2

Abstract: XRCC2 genetic variants have been associated with breast cancer susceptibility. However, association studies have been complicated because XRCC2 variants are extremely rare and consist mainly of amino acid substitutions whose grouping is sensitive to misclassification by the predictive algorithms. We therefore functionally characterized variants in XRCC2 by testing their ability to restore XRCC2-DNA repair deficient phenotypes using a cDNA-based complementation approach. While the protein-truncating variants p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…It also forms a heterodimer complex with other members of the RAD51 protein family such as RAD51B, RAD51C, RAD51D, XRCC3, BRCA1, and BRCA2. This heterodimer is needed for the localization of RAD51, which plays a key role in mediating HRR at DSB sites [ 30 , 31 ]. It is postulated that disruption of DSB repair contributes to carcinogenesis through the accumulation of genetic errors and genetic instability [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also forms a heterodimer complex with other members of the RAD51 protein family such as RAD51B, RAD51C, RAD51D, XRCC3, BRCA1, and BRCA2. This heterodimer is needed for the localization of RAD51, which plays a key role in mediating HRR at DSB sites [ 30 , 31 ]. It is postulated that disruption of DSB repair contributes to carcinogenesis through the accumulation of genetic errors and genetic instability [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…XRCC2 overexpression has also been identified as a marker for radioresistance, with knockdown causing enhanced sensitivity [135]. Mutation was initially associated with breast cancer development [136], however this has recently been disputed, and remains controversial [137,138]. Knockdown of XRCC2 is also known to cause sensitivity to PARP inhibitors [139].…”
Section: Homologous Recombination Fa Proteinsmentioning
confidence: 99%
“…In the largest study to date, of 13,087 breast cancer and 5,488 control cases from the UK, a total of 11 truncating and 32 rare missense variants were found (Decker et al, 2017). A recent study functionally characterized breast cancer-associated variants and found that each of the truncating or frameshift variants displayed compromised activity, while most of the missense variants tested displayed a minor change or no change in activity (Hilbers et al, 2016). Notably, a bi-allelic germ-line nonsense mutation in XRCC2 c.643C>T encoding p.R215X is causative for the U complementation group of Fanconi anemia, FA-U (Park et al, 2016; Shamseldin et al, 2012).…”
Section: Mutationsmentioning
confidence: 99%
“…However, no other study so far has confirmed mutation of XRCC2 as a significant cause of inherited breast cancer (Hilbers et al, 2016; Hilbers et al, 2012; Pelttari et al, 2015). For example, Hilbers et al analysed the coding region of 3548 non-BRCA1/2 familial breast cancer cases and 1435 healthy controls (Hilbers et al, 2012).…”
Section: Implicated Inmentioning
confidence: 99%